Poverty and inequality in Asia: 1965-2014 - Guanghua Wan; Chen Wang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
This paper aims to depict the post-Second World War poverty and inequality trends in Asia, its sub-regions, and individual economies. Efforts are made to explain these trends and explore the interrelationship between growth, poverty, and inequality in Asia. Analytical results confirm significant reductions in poverty across the board due to fast growth, although the benign effect of growth on poverty was offset by worsening distribution in many economies. Looking ahead, Asia is expected to eradicate poverty but likely to continue facing high inequality, particularly as major technology breakthroughs such as artificial intelligence and the internet of things replace more and more labour.
Keywords: O1; O53; R1; R58; 330; inequality; poverty; poverty-growth-inequality triangle; Asia